Pendampingan Peningkatan Kapasitas Skill Microsoft Word Guru Di SD Negeri 173529 Tampahan Kabupaten Toba Samosir - Sinta Dameria SImanjuntak; Ari Usman (LPPM Universitas Yudharta Pasuruan, 2019)
The problem of partners in Community Service Activities is that teachers are not able to operate computers or laptops properly. As a result of these conditions, the teacher is unable to use Microsoft Word smoothly. On the other hand, the use of Microsoft Word is very necessary for teachers both for administrative purposes, the need for the preparation of scientific work or the preparation of teaching materials. The solution used to overcome partner problems is through Microsoft Word learning activities. The learning method implemented is through group discussions, deliberations, internal training and workshops. The results obtained were an increase in partner knowledge in operating Microsoft Word and the teacher gave a positive response to the training activities.